The emigrants - Moberg, Vilhelm 1898-1973; Nordgren, Erik 1913-1992 (The Criterion Collection, 2016)
A monumental mid-nineteenth century epic that charts, over the course of two films, a poor Swedish farming family's voyage to America and their efforts to put down roots in this beautiful but forbidding new world. Includes bonus disc with special features
Original: Schweden 1971, 1972
director-approved three-DVD special edition features: new high-definition digital restorations of both films ; new introduction by theater and film critic John Simon ; new conversation between film scholar Peter Cowie and director Jan Troell ; new interview with actor Liv Ullmann ; "To paint with pictures", an hour-long documentary from 2005 on the making of the films, featuring archival footage as well as interviews with Troell, Ullmann, producer and coscreenwriter Bengt Forslund, actor Eddie Axberg, and composer Georg Oddner ; trailers ; new English subtitle translations ; plus: an essay by critic Terrence Rafferty
Bildformat 1.66:1
Keywords: Moberg, Vilhelm / 1898-1973 / Film adaptations; Moberg, Vilhelm / 1898-1973; Geschichte 1800-1900; Immigrants / Minnesota / History / 19th century / Drama; Swedes / Minnesota / History / 19th century / Drama; Swedish Americans / Minnesota / History / 19th century / Drama; Immigrants; Swedes; Swedish Americans; Einwanderer; Geschichte; Minnesota; Film; DVD-Video